PENGARUH METODE PEMBELAJARAN BERBASIS MASALAH TERHADAP KEMAMPUAN MENULIS PUISI SISWA KELAS X SMA PERSIAPAN AEK NABARA TAHUN PELAJARAN 2019/2020 - ANNIM HASIBUAN (JURNAL ILMIAH KOHESI, 2020)
The problem in this study is whether there is an influence of problem-based learning methods on the ability to write poetry grade X students SMA Aek Nabara year of learning 2019/2020?. The purpose in this study was to describe the influence of problem-based learning methods on the ability to write poetry grade X students SMA Aek Nabara Preparatory Year 2019/2020 learning. The method used in the research is the quasi experiment method to find data on whether there is a difference between the two groups. This method is used to observe the influence of problem-based learning (PBM) methods on student poetry writing skills. Therefore, the experiment group was tested with PBM methods while the control group was in test with conventional methods. The population in this study was a grade X student of Aek Nabara High School preparatory year 2019/2020 learning amounting to 110 people with a sample of 72 students, then the samples were divided into two groups, namely the group of experiments and control groups that numbered 36 people each. The instrument used in data collection is a test essay, where students are told to write poetry according to the criteria that had been described by previous researchers. The results showed that there was an influence of problem-based learning (PBM) methods on the ability to write poetry grade X students SMA Aek Nabara year lesson 2019/2020. From the comparative calculation of a significant standard value = 0.05 with DK 36-2, obtained a value of T 0.05 (34) between 2.021-2,000, the value of Thitung > This (16.80 > 2,021 – 20,000). This means an alternative hypothesis is acceptable. Thus a problem-based learning method can improve the writing ability of poetry students grade X SMA Prep Aek Nabara year lesson 2019/2020.